M-Shaped Conformal Antenna with FSS Backing for Gain Enhancement - Madhavi Devi Lanka; Subbarao Chalasani (Engineering Proceedings)
A frequency selective surface (FSS) integrated conformal antenna is modelled and analytical study is presented in this article. A novel antenna design known as the “M-shaped Conformal Antenna with FSS Backing for Gain Improvement” makes use of both the conformal structure and FSS technology to increase gain. The geometric shape of the M-shaped antenna, which might resemble the letter “M” or a collection of M-shaped parts, is what gives it its name. This structure can be created to alter the antenna’s resonance frequency, increase bandwidth, or adjust the emission pattern. The radiation pattern of the antenna may be precisely controlled by combining an M-shaped construction with an FSS. You may customize the radiation pattern to concentrate energy in particular directions or sectors, boosting gain and coverage, when necessary, by modifying the FSS’s geometry and physical characteristics. The combination of features makes it extremely ideal for a variety of applications where optimum gain is a crucial need, such as aerospace, communications, and radar arrays. It also enables fine control of the radiation pattern, frequency-selective gain, and interference elimination. The designed antenna consists of an M-shaped model on the visible sideways along with a complement split ring resonator and a defective ground structure on the bottom side. Antenna resonating at wideband cover several lower band wireless communication applications like Bluetooth, Wireless Fidelity (Wi-Fi), Manufacturing Communication and Pharma, Long Term Evolution-LTE, advanced 5G, and Wireless LAN with impedance bandwidth of 65%. The FSS beneath the antenna structure acts as reflector and providing additional gain and efficiency improvement of 22% and 12%, respectively. The prototype measurement supporting the simulation results with good matching in reflection coefficient and gain.